MOTIVASI KERJA, KEPUASAN KERJA DAN KINERJA PEGAWAI TENAGA KONTRAK - Mashur Fadli (Universitas Riau, 2017)
Abstract: Work Motivation, Job Satisfaction and Employee Performance Power Contract.The research objective is to investigate and analyze the influence of motivation and job satisfactionto employee performance contract staff Faculty of Social and Political Sciences, Universityof Riau. This type of research is quantitative descriptive with a population of 63 people and allsampled in the study. Data collection techniques using interviews and questionnaires. Hypothesistesting using multiple linear regression analysis method using a confidence level of 95%. Theresults showed that simultaneously work motivation and job satisfaction have a significant effecton employee performance contract workers. Partially each of the variables significantly influenceemployee performance contract workers. Work motivation is the factor most dominant influenceon employee performance contract workers, meaning that work motivation play a bigger rolein determining the performance of contract labor employees. Regression test results of researchshow that, the value of determination coefficient of 0.598. What this means is that the contributionof the influence of independent variables on the dependent variable is equal to 59.8%. Whilethe remaining 40.2% is influenced by other variables not included in this regression model.